The Impact of Work-Life Balance on Job Engagement and Turnover Intention - Jaharuddin, Nor Siah; Zainol, Liyana Nadia (The South East Asian Journal of Management, 2019)
Research Aims: Work-life balance (WLB) and employee engagement are regarded as factors or catalysts with the potential to ensure a firm's continuous growth. Hence, imbalance between work and personal life causes higher stress that might lead to greater turnover intention among employees. As such, employees' ability to achieve WLB with organisational support should lead to higher job engagement, commitment and better job performance. This study examines a holistic view of the link between WLB, job engagement and turnover intention. Design/Methodology/Approach: Data was gathered using a quantitative study by distributing a questionnaire survey to 213 executive employees in Klang Valley, Malaysia. Research Findings: Interestingly, the findings revealed a direct relationship between work-life conflicts and job engagement and turnover intention. There is also a significant correlation of job engagement to employees' turnover intention. However, no mediation effect of job engagement is found between WLB and turnover intention. Theoretical Contribution/Originality: This study links all the three variables-WLB, job engagement and turnover intention-in a holistic way. Managerial Implications in the Southeast Asian Context: It is imperative to have WLB practices in organisations to support employees in order to ensure their well-being and thus, increase their engagement and retention. These findings, discovered among executives in Malaysia, provide recommendations to practitioners on this topic, including companies and regulatory bodies. Research Limitations and Implications: Most of the samples were drawn from the millennial generation; their expectations towards work life intervals might be different from mature adults.